Cinema of the dark side : atrocity and the ethics of film spectatorship - Chaudhuri, Shohini (Edinburgh University Press, 2014)
A ground-breaking comparative treatment of cinematic images of atrocity, combining critical perspectives on contemporary film and human rights. A few days after 9/11, US Vice-President Dick Cheney invoked the need for the USA to work 'the dark side' in its global 'War on Terror'. Cinema of the Dark Side explores how contemporary cinema treats state-sponsored atrocity, evoking multiple landscapes of state terror. Investigating the ethical potential of cinematic atrocity images, this book argues that while films help to create and confirm normative perceptions about atrocities, they can also disrupt those perceptions and build alternatives. Asserting a crucial distinction between morality and ethics, a new conceptualisation of human rights cinema is proposed, one that repositions human rights morality within an ethical framework that reflects upon the causes and contexts of violence. It builds upon theories of embodied spectatorship to offer a new perspective on the ethics of spectatorship, providing readers with fresh insights into how we respond to atrocity images and the ethical issues at stake. Covering a diverse spectrum of 21st century cinema, this books deals with documentary or fictional representations of atrocity such as state-sanctioned torture, genocide, enforced disappearance, deportation, and apartheid. Case studies include:. Zero Dark Thirty (2012), Standard Operating Procedure (2008), Hotel Rwanda (2004), Sometimes in April (2005), Nostalgia for the Light (2010), Chronicle of an Escape (2006), Children of Men (2006), District 9 (2009), Waltz With Bashir (2008), and Paradise Now (2005). Key Features. A comprehensive treatment of cinematic images of atrocity as a genre, featuring close, comparative analysis of recent films A unique perspective on the ethics of spectatorship, based upon a multi-sensory approach to the film medium A critical introduction to debates on cinematic identification